Defining and operationalizing the phenomena of recovery: a working definition from the recovery science research collaborative. (4th May 2019) - Ashford, Robert D.; Brown, Austin; Brown, Tiffany; Callis, Jason; Cleveland, H. Harrington; Eisenhart, Emily; Groover, Hillary; Hayes, Nicholas; Johnston, Teresa; Kimball, Thomas; Manteuffel, Brigitte; McDaniel, Jessica; et al.
Abstract: A number of definitions exist for the concept of "recovery" in both the substance use disorder (SUD) and mental health (MH) fields. Previous attempts to define recovery have not reached consensus among experts within the field. Thus, the definition has remained diffuse at the expense of attempts to measure and evaluate treatment and recovery outcomes. The notion of recovery as an organizing principle between SUD and MH, collectively identified as behavioral health (BH), can be better served by a collaborative endeavor to define the word and concept of "recovery". The Recovery Science Research Collaborative (RSRC), an interdisciplinary bi-annual collaboration among recovery researchers and professionals from across the country, sought to address the definition of recovery at the inaugural meeting in December 2017 at Kennesaw State University. The RSRC undertook this task with the primary goal of defining "recovery" for use in research – aiming to create a consensus definition that allows recovery to be clearly operationalized and effectively investigated.